Manajemen Pendidikan Islam di Mualaf Qur`an Center Sumatera Barat - Rizki Ramadani; Faiz Fauzan Elmuhammady; Zulfikri Zulfikri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Converts often experience difficult in participating in Islamic education. In order to better organize Islmic education being studied, it is felt necessary to consider management issues in the educational process. Managemen is very influential in providing knoeledge to converts who want to learn the basics of Islamic education. One environment that can be used as an alternative to improve Islamic education for converts is the Qur'an Convers Center West Sumatra, this is a organization under foundation of the Qur`an Convers Indonesia in Yogyakarta. Therefore researchers are interested in examining how Islamic education is managed at the Qur'an Center Converts West Sumatra. This research uses a qualitative method where data collection uses interview, observation and documentation techniques, then the data is processed into descriptive descriptions. Islamic education management applied by the Qur'an Convers Center West Sumatra has fulfiled the elements and functions of management. Starting from element of management (Man, Money, Materials, Machines, Methods,). While the management functions (Planning, Organizing, Actuating, Controling). The inhibiting factors in the Qur'an Convers Center West Sumatra are: the loss of news of converts, converts and coaches who have other activities and still lack funds in terms of operations. Apart from that, there are supporting factors, there are: collaborating with Provincial institutions and other humanitarian organizations, utilizing information technology, and having permanent and non-permanent donors.